2012
DOI: 10.1371/journal.pgen.1002800
|View full text |Cite
|
Sign up to set email alerts
|

A Broad Requirement for TLS Polymerases η and κ, and Interacting Sumoylation and Nuclear Pore Proteins, in Lesion Bypass during C. elegans Embryogenesis

Abstract: Translesion synthesis (TLS) polymerases are specialized DNA polymerases capable of inserting nucleotides opposite DNA lesions that escape removal by dedicated DNA repair pathways. TLS polymerases allow cells to complete DNA replication in the presence of damage, thereby preventing checkpoint activation, genome instability, and cell death. Here, we characterize functional knockouts for polh-1 and polk-1, encoding the Caenorhabditis elegans homologs of the Y-family TLS polymerases η and κ. POLH-1 acts at many di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 56 publications
1
55
2
Order By: Relevance
“…S1B). This observation is consistent with studies of POLH-1 during C. elegans embryogenesis and suggests that functional redundancy among Yfamily polymerase members may account for the lack of severe phenotypes in single mutants (Roerink et al, 2012).…”
Section: Drosophila Y-family Polymerases Are Expressed In Early Embryossupporting
confidence: 90%
See 1 more Smart Citation
“…S1B). This observation is consistent with studies of POLH-1 during C. elegans embryogenesis and suggests that functional redundancy among Yfamily polymerase members may account for the lack of severe phenotypes in single mutants (Roerink et al, 2012).…”
Section: Drosophila Y-family Polymerases Are Expressed In Early Embryossupporting
confidence: 90%
“…C. elegans POLH-1 is regulated by sumoylation, which protects it from degradation during lesion bypass (Roerink et al, 2012). POLH-1 ubiquitylation presumably occurs after it has successfully bypassed the lesion and results in ubiquitin-mediated proteolysis by the CRL4-Cdt2 E3 ligase (Kim and Michael, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also for this exogenous source of DNA damage, animals deficient for both pol eta and pol kappa are profoundly more sensitive than animals deficient for only pol eta, whereas pol kappa disruption by itself only very mildly increases the sensitivity of wild-type worms. (Roerink et al 2012). Under nonchallenged conditions, we found deletion junctions to preferentially result from replication fork stalling at dG residues (Fig.…”
Section: Discussion Tls Polymerases Eta and Kappa Operate On Endogenomentioning
confidence: 69%
“…In previous work, we established the role of the C. elegans homologs of TLS polymerases pol eta (POLH-1) and pol kappa (POLK-1) in the protection against a wide range of exogenous DNA damaging agents (Roerink et al 2012). In these studies, we also sporadically observed readily recognizable mutant phenotypes during normal culturing of polh-1polk-1 double mutant animals, which prompted us to suspect a prominent role for these Y-family TLS polymerases in the prevention of spontaneous mutations (Supplemental Fig.…”
Section: Tls Polymerases Protect Genomes Against Spontaneous Deletionsmentioning
confidence: 99%
“…Injection marker plasmids pGH8 and pCFJ104 (used for lfIs177) are described in the study by Frøkjaer-Jensen et al 42 Immunostainings and RAD-51 foci quantification. Germlines were dissected from young adults (1 day post-L4 stage) and processed for immunostaining 43 . Samples were incubated overnight at room temperature with primary anti-RAD-51 antibodies (Novus Biologicals no.…”
Section: Methodsmentioning
confidence: 99%